Transformations in risk management of currency exchange in Lithuanian commercial banks - Nedzvedskas, Jonas; Aniūnas, Povilas (Technological and Economic Development of Economy, 2007)
After the adoption of International Convergence of Capital Measurement and Capital Standards (widely known as Basel II requirements) in 2004 the risk management in commercial banks has changed dramatically. Lithuanian commercial banks are in transitional period now adapting their risk management systems to Basel II requirements. Market risk is considered one of the key risks in bank risk management structure, so proper management of market risk is essential for a modern bank. Currency exchange risk usually is the main component of market risk. Currency exchange risk management in Lithuanian commercial banks was not good enough; also the Central Bank's regulatory limits were liberal. But after the adoption of Basel II requirements, the entire risk management system is transforming and currency exchange risk management is affected. The objective of this paper is to demonstrate the transformations of currency exchange in Lithuanian commercial banks and propose an effective model for commercial banking. These transformations are performed in the regulatory system imposed by the Central Bank of Lithuania and through transformations of the bank's internal risk management system moving to internal (usually VaR based) models. VaR models are considered as modern methods for risk management. These models proposed by Central bank or other authorities for internal and statutory risk management in commercial banks. In this article, the proposed variation‐covariation VaR model was tested with real data using the back‐testing method. Back‐testing showed that the proposed model is reliable enough, because the number of mismatches was less than 5% in all tested currency pairs during all testing. In most currency pairs mismatches percentage was lower than 3%. Back‐testing results confirm that the VaR method is reliable enough for day‐to‐day using by financial institutions and traders.Valiutų keitimo rizikos valdymo transformacijos Lietuvos komerciniuose bankuoseSantrauka. Straipsnyje pateikiamas naujas vertės rizikos (VR) modelis valdant valiutų keitimo riziką. Tai buvo išbandyta realiomis rinkos sąlygomis Lietuvos komerciniuose bankuose. Daroma išvada, kad pasiūlytas metodas yra veiksmingesnis negu buvę valiutų keitimo rizikos valdymo metodai, kuriuos Lietuvos bankas pritaikė pagal Bazelio II nuostatas.Reikšminiai žodžiai: valiutos keitimo rizika, vertės rizika (VR), Bazelio komitetas, komercinė bankininkystė, Lietuva.First Published Online: 21 Oct 2010